«Երեք չափերի» սկզբունքները «Հաճախապատում ճառք»-ում - Սամվել Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Такие принципы и методы зороастрийских, а позже и христианских правовых, нравственных, религиозных, экономических, политических и эстетических идейно-регулятивных нормативных систем, как «Три меры» или «Триады» – «Добрая мысль, доброе слово, доброе дело» и «Злая мысль, злое слово, злое дело», встречаются как во всех структурных частях Авесты, так и в «Частоповторяемых речах» Григория Просветителя. Such principles and methods of Zoroastrian, and later Christian legal, moral, religious, economic, political and aesthetic ideological-regulatory normative systems, as the “Three measures” – or “Triads” – “Good thought, good word, good deed” and “Evil thought, evil word, evil thing” occur both in all structural parts of Avesta and in the “Frequently Repeated Speeches”of Gregory the Illuminator.
Keywords: B Philosophy; Psychology; Religion; B Philosophy; BL Religion